M-learning and Its Effects On Learning Arabic As Second Language for Engineering Students - Mohammad Baihaqi, Hasni (JHLCB, 2017)
The article deals with the importance of learning through mobile apps known as M-learning. The M-learning is a software application designed to run on mobile devices such as smartphones and tablet computers to assist the learning of Arabic as a second language to engineering students. This application is beneficial since the amount of information to be accessed in university has increased significantly in recent years. Students nowadays are moving towards using a smart phone as a means of information in the learning process. Mobile technologies and approaches are also used to assist in language learning. A smart phone is a multifunctional device that not only communicates, but helps to learn, earn, and have fun. This is made possible by the development of mobile applications. The sample was obtained through the result of the examination that have been conducted on undergraduate students taking courses in Arabic for Beginners during the first semester of 2016/2017. The study was conducted on 30 engineering students of Universiti Malaysia Pahang. This study used the qualitative and quantitative approaches. The article also presents the advantages, disadvantages and some examples of online platforms that offer Arabic courses. M-learning is a new method, a relatively new concept in the learning process. M-learning means that learning is not configured to a study table only, nowadays students should have constant access to information regardless wherever they are. The conclusion is that M-learning cannot completely replace the classical methods of learning, but can facilitate and improve the learning process.